2007
DOI: 10.1186/1471-213x-7-87
|View full text |Cite
|
Sign up to set email alerts
|

Apoptosis in mouse fetal and neonatal oocytes during meiotic prophase one

Abstract: Background: The vast majority of oocytes formed in the fetal ovary do not survive beyond birth. Possible reasons for their loss include the elimination of non-viable genetic constitutions arising through meiosis, however, the precise relationship between meiotic stages and prenatal apoptosis of oocytes remains elusive. We studied oocytes in mouse fetal and neonatal ovaries, 14.5-21 days post coitum, to examine the relationship between oocyte development and programmed cell death during meiotic prophase I.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
60
0
3

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(72 citation statements)
references
References 56 publications
(76 reference statements)
9
60
0
3
Order By: Relevance
“…Oocyte loss and cyst breakdown begin after birth in the cortical region of the ovary, but in the medullary region, these processes begin as early as 17.5 dpc (Pepling et al 2010). This is similar to other studies on the mouse and also on humans where oocyte loss has been observed during fetal development (De Pol et al 1997, De Felici et al 1999, McClellan et al 2003, Ghafari et al 2007). In the rat, follicles are first observed in the core of the ovary and formation gradually shifts toward the surface (Rajah et al 1992).…”
Section: The Process Of Follicular Assemblysupporting
confidence: 76%
“…Oocyte loss and cyst breakdown begin after birth in the cortical region of the ovary, but in the medullary region, these processes begin as early as 17.5 dpc (Pepling et al 2010). This is similar to other studies on the mouse and also on humans where oocyte loss has been observed during fetal development (De Pol et al 1997, De Felici et al 1999, McClellan et al 2003, Ghafari et al 2007). In the rat, follicles are first observed in the core of the ovary and formation gradually shifts toward the surface (Rajah et al 1992).…”
Section: The Process Of Follicular Assemblysupporting
confidence: 76%
“…The strains of mice used by these authors (C57BL and ICR wild-type (WT) female mice respectively) may be significant since variation in oogonial loss is thought to be heavily dependent on genotype. The germ cells lost during these waves before the formation of oocytes in primordial follicles exhibit nuclear condensation, cell shrinkage and fragmentation, and DNA laddering with positive TUNEL staining, and PARP1 immunoreactivity, all of which are characteristics typically associated with apoptosis (Coucouvanis et al 1993, Pesce & De Felici 1994, Pepling & Spradling 2001, Ghafari et al 2007, Lobascio et al 2007a, 2007b.…”
Section: Establishment Of the Ovarian Pool Of Primordial Folliclesmentioning
confidence: 99%
“…In females, meiosis is initiated around 13.5 dpc and oocytes progress in a relatively synchronous way through the four phases of prophase I (leptotene, zygotene, pachytene, and diplotene), which are mostly completed during fetal development (17,19,43) (Fig. 3A).…”
Section: Vol 31 2011 Hsf1 Role As a Meiotic Transcription Factor 3413mentioning
confidence: 99%